Potential Use of Brazilian Green Propolis Extracts as New Photosensitizers for Antimicrobial Photodynamic Therapy against Cariogenic Microorganisms - de Oliveira, Analú Barros [UNESP] (2023)
The synergic effect of Streptococcus mutans and Candida albicans increases dental caries severity. Antimicrobial photodynamic therapy (aPDT) is a non-invasive treatment for antimicrobial aspects. However, the current photosensitizers (PS) have many downsides for dental applications. This study aimed to evaluate the efficiency of two different Brazilian green propolis (BGP-AF and BGP-AG) as PS for aPDT against these microorganisms. A single-species biofilm was irradiated with crude extracts and their fractions and controls. Such extracts showed the best results and were evaluated in dual-species biofilms. Photodegradation, reactive oxygen species (ROS), cytotoxicity, and color stability assays were also investigated. Reductions higher than 3 log10 CFU/mL (p < 0.0001) occurred for crude BGP in single- and dual-species biofilms. Singlet oxygen was produced in BGP (p < 0.0001). BGP-mediated aPDT delayed S. mutans and C. albicans regrowth after 24 h of treatment (p < 0.0001). Both BGP did not change the color of dental materials (p > 0.05). BGP-AF-mediated aPDT showed 72.41% of oral keratinocyte viability (p < 0.0001). BGP extracts may be used in aPDT against S. mutans and C. albicans. Specifically, BGP-AF may represent a promising PS for dental applications.